Effect of nanoclay supported nanosilver on the growth inhibition of aquatic pathogens and immunomodulatory effect in Penaeusvannamei. Issue 135 (April 2023) - Liao, Zhen-Hao; Huang, Huai-Ting; Lin, Yu-Ru; Hu, Chi-Yun; Kai, Yu-Hsuan; Lin, Jiang-Jen; Nan, Fan-Hua
Abstract: Hybrid of nanosilver and nanoscale silicate platelet (AgNSP) is a safe, non-toxic nanomaterial which has been applied in medical use due to its strong antibacterial activity. The application of AgNSP in aquaculture was first proposed in the present study by evaluating the in vitro antibacterial activities against four aquatic pathogens, in vitro effects toward shrimp haemocytes as well as the immune responses and disease resistance in Penaeus vannamei fed with AgNSP for 7 days. For evaluating the antibacterial activities of AgNSP in culture medium, the minimum bactericidal concentration (MBC) values against Aeromonas hydrophila, Edwardsiella tarda, Vibrio alginolyticus and Vibrio parahaemolyticus were 100, 15, 625 and 625 mg/L, respectively. Moreover, the inhibition of pathogen growth over a period of 48 h could be achieved by the appropriate treatment of AgNSP in culturing water. In freshwater containing bacterial size of 10 3 and 10 6  CFU/mL, the effective doses of AgNSP against A. hydrophila were 12.5 and 450 mg/L, respectively while the effective doses against E. tarda were 0.2 and 50 mg/L, respectively. In seawater with same bacterial size, the effective doses against V. alginolyticus were 150 and 2000 mg/L, respectively while the effective doses against V. parahaemolyticus were 40 and 1500 mg/L, respectively. For the in vitro immune tests, the superoxide anion production and phenoloxidase activity in haemocytes were elevated after in vitro incubation with 0.5–10 mg/L of AgNSP. In the assessment of dietary supplemental effects of AgNSP (2 g/kg), no negative effect on the survival was found at the end of 7 day feeding trail. In addition, the gene expression of superoxide dismutase, lysozyme and glutathione peroxidase were up-regulated in haemocytes taken from shrimps received AgNSP. The following challenge test against Vibrio alginolyticus showed that the survival of shrimp fed with AgNSP was higher than that of shrimp fed with control diet ( p  = 0.083). Dietary AgNSP improved the Vibrio resistance of shrimp by increasing 22.7% of survival rate. Therefore, AgNSP could potentially be used as a feed additive in shrimp culture. Highlights: Nanoscale silicate platelet supported nanosilver (AgNSP) is applied in aquaculture. AgNSP has antibacterial activities against aquaculture pathogens. AgNSP enhance O2 − production and phenoloxidase activity in shrimp haemocytes. Dietary AgNSP cause immunomodulatory effects in Penaeus vannamei. Dietary AgNSP increase shrimp resistance against Vibrio alginolyticus.